Drill cutting release in Ingøydjupet, SW Barents Sea from a well drilled in 1987, and its impact on benthic foraminifera - Berg, Julie (UiT Norges arktiske universitet, 2017)
In the nearby areas of the SW Barents Sea, large hydrocarbon reserves have been identified. During drilling procedures, drill cuttings are produced and some are released to sea. The disposal of drill cuttings may cause environmental degradation to the marine environment. Increasing petroleum activities, therefore requires further knowledge of ocean current transportation of fine sediment particles (clay and silt) related to cuttings and their effect on the marine environment and fauna including benthic foraminifera. Here, benthic foraminiferal assemblages and heavy metal concentrations in five different cores along a transect away from a well drilled in 1987 in the Ingøydjupet trough are presented. Elevated metal concentrations of Ba, Pb, Hg and Cu where found in core T 10-4, closest to the pollution source. This core also has a low total number of foraminiferal specimens, which indicates this core is most impacted by drill cutting release. Cores further away reveals heavy metal concentrations that correspond to background levels, and foraminiferal assemblages that correspond to previous studies of pre-impacted foraminiferal assemblages in Ingøydjupet. Patterns in the foraminiferal assemblages in these cores, suggest natural variability related to a stronger inflow of Atlantic water with enhanced food supply. This study provides information about the impact of drill cutting release to the marine environment, and evaluates what can be done to prevent environmental impact of discharges of drill cuttings, alternative solutions for discharges, as well as which approaches can be used for removal of drill cuttings that has already been released to the marine environment.